CONCEPTION OF ISLAMIC RELIGIOUS EDUCATION (PAI) ON EVOLUTION CONCEPT - Susanti Wulandari; Nuryani Y. Rustaman; Ari Widodo; I Nyoman Pugeg Aryantha (IAIN Ternate, 2020)
Evolution is one of the content that is considered controversial in science because many people do not agree with the theories of evolution. This study aims to investigate the perceptions of Islamic religious education students’ regarding the concepts of evolution. This descriptive research was conducted through a survey method to 288 first-level students’ at a private university in Tasikmalaya Regency, West Java. The findings show that most of the PAI students’ have a wrong understanding of the concept of evolution. Based on the results of the interview, the fact is that this is due to the knowledge obtained at the previous level. This research indicates that there are still many misconceptions that occur in students’, including science or biology teachers who teach evolutionary material at the secondary school level.Keywords: misconception, evolution concept, Islamic religious education